KAJIAN KERENTANAN SOSIAL EKONOMI MASYARAKAT LOKAL TEMBALANG TERKAIT PROSES STUDENTIFIKASI DI KAWASAN PENDIDIKAN TINGGI TEMBALANG - Zahratul Hayah; Santi Paulla Dewi (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2020)
The high number of students due to the Tembalang Higher Education Area triggered the phenomenon of studentification. Studentification has various impacts. People who are unable to cope with and recover from the pressures and impacts caused by the studentification process are called vulnerable communities. This study aims to analyze local community’s social economic vulnerability in dealing with studentification process in the Tembalang Higher Education Area and how the community's adaptive response forms. Achieving the objectives of this study was carried out using qualitative research methods. The result was identified pressure that faced by the community is the high price of land and the inability of the community to expand their land in the Tembalang Higher Education Area. While the form of community response is illustrated by the attitude of social and economic adaptation of the community in the Tembalang Higher Education Area, such as changing jobs, moving outside the Tembalang Higher Education Area but still working in the Tembalang Higher Education Area as a commuter, and applying for a loan that is used as asset to work or open a new business field.